2021
DOI: 10.4014/jmb.2106.06006
|View full text |Cite
|
Sign up to set email alerts
|

Codon Optimization, Soluble Expression and Purification of PE_PGRS45 Gene from Mycobacterium tuberculosis and Preparation of Its Polyclonal Antibody Protein

Abstract: Studies have demonstrated that PE_PGRS45 is constitutively expressed under various environmental conditions (such as nutrient depletion, hypoxia, and low pH) of the in vitro growth conditions examined, indicating that PE_PGRS45 protein is critical to the basic functions of Mycobacterium tuberculosis. However, there are few reports about the biochemical function and pathogenic mechanism of PE_PGRS45 protein. The fact that this M. tuberculosis gene is not easily expressed in E. coli may be mainly due to the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Using Mtb H37Ra genomic DNA as a template, the target gene was obtained by PCR amplification, and the primers are shown in Additional file 1 : Table S1. We inserted the target gene into the vector pET-28a using the homologous recombination cloning technique [ 27 ]. The obtained 12 recombinant plasmids were confirmed by colony PCR and DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Mtb H37Ra genomic DNA as a template, the target gene was obtained by PCR amplification, and the primers are shown in Additional file 1 : Table S1. We inserted the target gene into the vector pET-28a using the homologous recombination cloning technique [ 27 ]. The obtained 12 recombinant plasmids were confirmed by colony PCR and DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…His-tagged recombinant proteins were purified by nitrilotriacetic acid (Ni–NTA) agarose resin (CWBIO, Jiangsu, China) according to previous reports [ 28 ] for purification of proteins under soluble conditions. First, the crude supernatant cell extract was filtered through a 0.45 μm filter.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Xu et al. purified PPE15 and found that it had strong antigenicity and could react specifically with the serum of patients suffering from TB but not with the serum of patients with pneumonia or healthy adults ( 102 ). Although few studies have been done on PPE15, those results suggest that PPE15 is a promising antigen target for developing vaccine candidates against TB, but the specific immune mechanism merits further exploration.…”
Section: Novel Vaccines Based On Pe/ppe Family Proteins Against Tbmentioning
confidence: 99%